Thermally Stable TiO2‐ and SiO2‐Shell‐Isolated Au Nanoparticles for In Situ Plasmon‐Enhanced Raman Spectroscopy of Hydrogenation Catalysts - Hartman, Thomas; Weckhuysen, Bert M. (Chemistry : a European journal, 2018)
Raman spectroscopy is known as a powerful technique for solid catalyst characterization as it provides vibrational fingerprints of (metal) oxides, reactants, and products. It can even become a strong surface‐sensitive technique by implementing shell‐isolated surface‐enhanced Raman spectroscopy (SHINERS). Au@TiO2 and Au@SiO2 shell‐isolated nanoparticles (SHINs) of various sizes were therefore prepared for the purpose of studying heterogeneous catalysis and the effect of metal oxide coating. Both SiO2‐ and TiO2‐SHINs are effective SHINERS substrates and thermally stable up to 400 °C. Nano‐sized Ru and Rh hydrogenation catalysts were assembled over the SHINs by wet impregnation of aqueous RuCl3 and RhCl3. The substrates were implemented to study CO adsorption and hydrogenation under in situ conditions at various temperatures to illustrate the differences between catalysts and shell materials with SHINERS. This work demonstrates the potential of SHINS for in situ characterization studies in a wide range of catalytic reactions. SHINERS nanostructures in action for the study of heterogeneous catalysts. Au nanoparticles are coated with ultrathin TiO2 or SiO2 coatings and subsequently assembled with transition‐metal catalysts, such as Ru, to enable the study of hydrogenation of CO. By using this method, various catalyst materials can be studied with improved sensitivity at the support–metal interface.